2019
DOI: 10.2965/jwet.18-048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salinity and Immobilization Period on the Nitrification and Denitrification Co-processes during Biofilter Acclimation in a Marine Recirculating Aquaculture System

Abstract: Biological filtration plays an important role in a sustainable recirculating aquaculture system. To provide the appropriate conditions for biofilter acclimation, the effects of the salinity and acclimation period on nitrogen removal and microbial diversity were evaluated. Nitrification rate (NR) of the shrimp tank biofilter increased during the first 4 weeks and decreased thereafter. The highest NR was found in the 5 PSU salinity tank at week 2, whereas in the other salinities (15 and 25 PSU) the highest NR wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In the case of marine/brackish RAS biofilters, studies have demonstrated the common occurrence of prevalent aerobic or facultatively anaerobic chemoorganotrophic genera such as Arenibacter , 67,88 Colwellia , 58,72 Gaetbulibacter , 54,72 Pseudomonas , 67,72,89 Pseudoalteromonas , 8,54,58,90 Vibrio , 21,54,57,58,67,89,91 Photobacterium 54 and Planctomyces 45,72 . Furthermore, there have been reports on the prevalence of the methylotrophic genus Methylotenera , 2,88 and the heterotrophic sulphur oxidizing genus Sulfitobacter 67 . Regarding the nitrifying community, the main ammonium oxidizers are Nitrosomonas , 2,5,19,44,45,62,68,72,86,89,92 Nitrosospira 31,86,89 and Nitrosopumilus , 19,44 while the prominent nitrite oxidizing genera are Nitrospira 45,62,67,72,86,88,89,93 which also includes comammox species, and to a lesser extend ‘ Candidatus Nitrotoga’, 5,31,86 Nitrospina 62,72,76 and Nitrobacter 5,44 …”
Section: Prokaryotic Diversity In Rasmentioning
confidence: 99%
See 4 more Smart Citations
“…In the case of marine/brackish RAS biofilters, studies have demonstrated the common occurrence of prevalent aerobic or facultatively anaerobic chemoorganotrophic genera such as Arenibacter , 67,88 Colwellia , 58,72 Gaetbulibacter , 54,72 Pseudomonas , 67,72,89 Pseudoalteromonas , 8,54,58,90 Vibrio , 21,54,57,58,67,89,91 Photobacterium 54 and Planctomyces 45,72 . Furthermore, there have been reports on the prevalence of the methylotrophic genus Methylotenera , 2,88 and the heterotrophic sulphur oxidizing genus Sulfitobacter 67 . Regarding the nitrifying community, the main ammonium oxidizers are Nitrosomonas , 2,5,19,44,45,62,68,72,86,89,92 Nitrosospira 31,86,89 and Nitrosopumilus , 19,44 while the prominent nitrite oxidizing genera are Nitrospira 45,62,67,72,86,88,89,93 which also includes comammox species, and to a lesser extend ‘ Candidatus Nitrotoga’, 5,31,86 Nitrospina 62,72,76 and Nitrobacter 5,44 …”
Section: Prokaryotic Diversity In Rasmentioning
confidence: 99%
“…Furthermore, there have been reports on the prevalence of the methylotrophic genus Methylotenera , 2,88 and the heterotrophic sulphur oxidizing genus Sulfitobacter 67 . Regarding the nitrifying community, the main ammonium oxidizers are Nitrosomonas , 2,5,19,44,45,62,68,72,86,89,92 Nitrosospira 31,86,89 and Nitrosopumilus , 19,44 while the prominent nitrite oxidizing genera are Nitrospira 45,62,67,72,86,88,89,93 which also includes comammox species, and to a lesser extend ‘ Candidatus Nitrotoga’, 5,31,86 Nitrospina 62,72,76 and Nitrobacter 5,44 …”
Section: Prokaryotic Diversity In Rasmentioning
confidence: 99%
See 3 more Smart Citations